Recent Progress in Inkjet-Printed Thin-Film Transistors - Chung, Seungjun; Cho, Kyungjune; Lee, Takhee (WILEY, 2019)
Drop-on-demand inkjet printing is one of the most attractive techniques from a manufacturing perspective due to the possibility of fabrication from a digital layout at ambient conditions, thus leading to great opportunities for the realization of low-cost and flexible thin-film devices. Over the past decades, a variety of inkjet-printed applications including thin-film transistors (TFTs), radio-frequency identification devices, sensors, and displays have been explored. In particular, many research groups have made great efforts to realize high-performance TFTs, for application as potential driving components of ubiquitous wearable electronics. Although there are still challenges to enable the commercialization of printed TFTs beyond laboratory-scale applications, the field of printed TFTs still attracts significant attention, with remarkable developments in soluble materials and printing methodology. Here, recent progress in printing-based TFTs is presented from materials to applications. Significant efforts to improve the electrical performance and device-yield of printed TFTs to match those of counterparts fabricated using conventional deposition or photolithography methods are highlighted. Moreover, emerging low-dimension printable semiconductors, including carbon nanotubes and transition metal dichalcogenides as well as mature semiconductors, and new-concept printed switching devices, are also discussed.
Keywords: FIELD-EFFECT TRANSISTORS; LOW-TEMPERATURE FABRICATION; WALLED CARBON NANOTUBES; HIGH-PERFORMANCE; HIGH-MOBILITY; P-TYPE; ORGANIC TRANSISTORS; HIGH-SPEED; POLYMER BLEND; OXIDE-FILMS